ANALISIS PERBEDAAN PENGARUH PREMI, KLAIM, DAN INVESTASI TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN ASURANSI SYARIAH DENGAN ASURANSI KONVENSIONALPERIODE 2011-2013 - Neneng Karyati; Sri Mulyati; Icih Icih (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2019)
The purpose of this study was to determine the effect of differences in premiums, claims and investment returns to profit growth. The population is Islamic insurance company with conventional insurance in Indonesia. Based on the purposive sampling method, the sample totaled 9 companies Takaful and conventional insurance companies 9 with the observation period 2011-2013. The analysis technique used is multiple regression analysis. Conclusion on Islamic insurance company is that premiums and investment returns no effect on profit growth, while the claims of positive effect on earnings growth. Whereas in conventional insurance companies is that the premium does not affect the profit growth, while the claims and investment returns positive effect on earnings growth.